Analisis Faktor-Faktor Yang Mempengaruhi Kehadiran Kaum Bapak Mengikuti Ibadah Minggu Di GKPPD Panji Bako - Rafenia Rahmayana M. Padang (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
The aim of this research is to determine the factors that influence the attendance of fathers at Sunday services at GKPPD Panji Bako as role models for GKPPD churches throughout Sitinjo District. The research method used is qualitative research. The technique for determining informants is purpose sampling based on certain criteria that are appropriate to the research topic. The data collection technique for this research is using semi-structured interviews and documentation in the form of images. Based on the results of research conducted by the author, the GKPPD Panji Bako fathers have an understanding of carrying out Sunday worship to continue to grow in faith and strengthen relationships with God and others. Sincerity in participating in worship must be accompanied by sincere intentions and sincerity of heart so that the meaning and benefits can be fully felt. There are two factors that influence fathers in attending Sunday worship, namely internal factors, factors that come from within the fathers, need factors and interest factors where feelings of joy and desire arise without any external encouragement. The second is external factors, factors that come from outside the fathers, namely the leadership of the pastor, the service of the servants, the church's worship arrangements, and the church's infrastructure (facilities). These two factors influence the presence of fathers in attending Sunday services so that fathers have an understanding and meaning of going to Sunday services.